2019
DOI: 10.1021/acsomega.9b02488
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties for Carbon Dioxide

Abstract: We first report three reliable analytical expressions of the entropy, enthalpy and Gibbs free energy of carbon dioxide (CO2) and perform predictions of these three thermodynamic quantities on the basis of the proposed analytical expressions and in terms of experimental values of five molecular constants for CO2. The average relative deviations of the calculated values from the National Institute of Standards and Technology database over the temperature range from 300 to 6000 K are merely 0.053, 0.95, and 0.070… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(43 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…The reduction of CO 2 into value-added molecules and fuels is a thermodynamically unfavorable process due to the high stability of the C=O bond (750 kJ mol −1 as compared with 411 kJ mol −1 for a C-H bond, for example) ( Wang et al., 2019 ). Given the large amount of energy needed to break the C=O bond, many research efforts have focused on developing solar-driven, or photocatalytic, processes that would facilitate the reduction of CO 2 ( Vogt et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of CO 2 into value-added molecules and fuels is a thermodynamically unfavorable process due to the high stability of the C=O bond (750 kJ mol −1 as compared with 411 kJ mol −1 for a C-H bond, for example) ( Wang et al., 2019 ). Given the large amount of energy needed to break the C=O bond, many research efforts have focused on developing solar-driven, or photocatalytic, processes that would facilitate the reduction of CO 2 ( Vogt et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 is considered as the main cause of the fluctuation of global climate. 36 Therefore, the reduction of carbon dioxide from the atmosphere is one of the the main concerns currently. The porous metal–organic materials are found as good sorbents for the CO 2 at mild pressure and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…3652 In the previous work, 53 our group investigated two analytical representations of the entropy and Gibbs free energy of carbon dioxide (CO 2 ) which is a triatomic linear symmetric molecule. Here, we further extend our treatment approach proposed in ref (53) to the triatomic linear nonsymmetric molecule COS. Span and Wagner 54 suggested that all the thermodynamic properties of a pure substance can be obtained by combining the Helmholtz free energy and its derivatives. Although Lemmon and Span 55 proposed an empirical analytical representation for the ideal-gas part of the Helmholtz free energy of COS, it contains 13 adjustable coefficients which were determined by fitting many experimental data points.…”
Section: Introductionmentioning
confidence: 99%